Comparison of Multiplate and VerifyNow platelet function tests in predicting clinical outcome in patients with acute coronary syndromes. Issue 152 (April 2017) - Larsen, Peter D; Holley, Ana S; Sasse, Alexander; Al-Sinan, Ali; Fairley, Sarah; Harding, Scott A
Abstract: Introduction: This study examined the ability of two widely used "point of care" platelet function assays, VerifyNow and Multiplate, to predict adverse outcomes in patients with acute coronary syndromes (ACS). Methods: We examined platelet reactivity using VerifyNow and Multiplate P2Y12 assays in patients with ACS and the relationship between platelet reactivity and both MACE (defined as a composite of death, myocardial infarction, stroke, stent thrombosis and unplanned revascularisation) and TIMI major bleeding at 1 year. Results: In 619 ACS patients, 65 patients (10.5%) had experienced MACE at 1 year and 6 patients (1%) had TIMI major bleeding events. The two measures of platelet reactivity were only moderately correlated (Rho = 0.43, p  = 0.0001). Both measures demonstrated a statistically significant relationship with MACE, with area under the curve for VerifyNow of 0.632 (0.001) and for Multiplate of 0.577 ( p  = 0.04), and neither measure showed a significant relationship with bleeding. Logistic regression analysis found that only VerifyNow was a statistical predictor of MACE ( p  = 0.01). MACE occurred in 16% of those classified as having HPR using VerifyNow compared to 7% in those without HPR (odds ratio of 2.6 (95% CI 1.5–4.4, p  = 0.001). In those classified as having HPR by the Multiplate assay, MACE occurred in 13% compared to 9% of those without HPR (Odds ratio 1.5 95% CI 0.9–2.5, p  = 0.11). Conclusion: The two points of care platelet function tests examined in this study were only moderately correlated. The VerifyNow assay demonstrated a stronger relationship to MACE than the Multiplate assay. Highlights: High on treatment platelet reactivity in ACS patients correlates with adverse outcomes. VerifyNow and Mutliplate assays produce different measures of platelet reactivity VerifyNow measured platelet reactivity was more predictive of adverse outcomes